Defeated Nation and Contested Womanhood : The Impact of the U.S. Occupation on the Reconstruction of National Identity in Postwar Japan - Endo, Masako (Asian Studies E-Books Online, Collection 2026., 2025)
This book investigates the impact of the U.S. occupation of Japan on the discursive remaking of Japanese womanhood. While exploring historical dynamics of Japanese femininity, it focuses on the context of the occupation in which meanings of gender, sexuality, race, and social class became particularly fluid. Drawing on insights from studies of gender, sexuality, race, and nation, Masako Endo considers how the occupation overtly sexualized and situationally or essentially racialized certain groups of people. She argues that they, by challenging traditional Japanese gender roles and sexual mores, shaped national discourses of Japanese womanhood and nationhood in occupied and post-occupation Japan.